Assessing working memory in general education students for ADHD detection (Research, Society and Development, 2021)
The involvement of deficient working memory in ADHD symptomatology has attracted intense research interest and has been scientifically substantiated. This fact provided an impetus for this study, which aims to investigate the role of working memory assessment in detecting ADHD elements in general education students in classroom settings. Therefore, 67 classroom teachers rated 130 Greek general education primary school students on the Greek-WMRS. The research findings indicated statistically significant differences in the overall score of the Greek-WMRS and in the separate score of its 20 descriptions of classroom behaviors between children clinically diagnosed with ADHD and those without. In conclusion, students’ working memory assessment in classroom settings can significantly contribute to detection of ADHD behaviors so that such classroom behaviors to be extensively assessed for an effective diagnosis.